Spatial and temporal localization of cell wall associated pili in Enterococcus Faecalis - Choo, Pei Yi (Nanyang Technological University, 2021)
Enterococcus faecalis relies upon a number of cell wall-associated proteins for virulence. One sortase-assembled virulence factor is the endocarditis and biofilm associated pilus (Ebp), an important factor for biofilm formation. The current paradigm for virulence factor assembly in Gram-positive bacteria is that Sortase A recognizes and cleaves at the LPXTG motif within its substrates and covalently attaches them to the growing cell wall at sites of new cell wall synthesis. While the cell wall anchoring mechanism and polymerization of Ebp is well characterized, less is known about the spatial and temporal deposition of this protein on the cell surface. We followed the distribution of Ebp and peptidoglycan (PG) at different growth stages of E. faecalis via immunofluorescence, along with fluorescent D-amino acids (FDAA) staining. Surprisingly, cell surface Ebp did not co-localize with newly synthesized PG. Instead, surface-anchored Ebp was localized to the cell hemisphere but never at the septum where new cell wall is deposited. In addition, the older hemisphere of mid-division cells was completely saturated with Ebp, while at the newer hemisphere, Ebp appeared as two foci directly adjacent to the newly synthesized PG. When cell wall synthesis was inhibited by ramoplanin, an antibiotic that inhibits lipid II, new Ebp was still deposited at the cell surface. Based on these data, we propose an alternative paradigm for sortase substrate deposition in E. faecalis, in which Ebp can be anchored directly onto uncross-linked cell wall, independent of cell wall synthesis.